2013
DOI: 10.1021/ja406893y
|View full text |Cite
|
Sign up to set email alerts
|

Facile Catch and Release of Fullerenes Using a Photoresponsive Molecular Tube

Abstract: A novel M2L2 molecular tube capable of binding fullerene C60 was synthesized from bispyridine ligands with embedded anthracene panels and Ag(I) hinges. Unlike previous molecular cages and capsules, this open-ended tubular host can accommodate a single molecule of various C60 derivatives with large substituents. The fullerene guest can then be released by using the ideal, noninvasive external stimulus, light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(109 citation statements)
references
References 43 publications
1
107
0
1
Order By: Relevance
“…several metal complexes able to host fullerenes and functionalized fullerenes (Fig. 29) [291][292][293][294].…”
Section: Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…several metal complexes able to host fullerenes and functionalized fullerenes (Fig. 29) [291][292][293][294].…”
Section: Supportmentioning
confidence: 99%
“…In addition, the functionalization of the ligands allows to modulate some proprieties of the complexes (solubility or crystallinity). Pd [291,293], Ag [292], and Hg [294] hosts systems have been proved to provide excellent encapsulation performances for fullerenes. Some of the capsules can release the fullerene using the appropriate stimulus.…”
Section: Supportmentioning
confidence: 99%
“…Solvents and reagents: TCI Co., Ltd., Wako Pure Chemical Industries Ltd., Kanto Chemical Co., Inc., Sigma-Aldrich Co., and Cambridge Isotope Laboratories, Inc. Compounds 6a , b and their precursors ( 5a , b ) (see Supplementary Methods and Supplementary Figs 2–6 and 19–22) were synthesized according to previously reported procedures2538.…”
Section: Methodsmentioning
confidence: 99%
“…Yoshizawa and co-workers synthesized an M 2 L 2 molecular tube capable of binding fullerene C 60 from bispyridine ligands with embedded anthracene panels and Ag(I) hinges. 26 This host was able to accommodate a single molecule of various C 60 derivatives with large substituents, which could then be released upon light irradiation. Tohnai and co-workers demonstrated that a cluster comprising anthracene-2-sulfonic acid and triphenylmethylamine changed its conformation in diamondoid porous organic salts via triggering by moisture.…”
Section: Supramolecular Programming For Energy and Chemical Conversionmentioning
confidence: 99%